Mastering mountain bike skills. - Lopes, Brian, ....-; McCormack, Lee, ....- (Champaign : Human Kinetics, 2010)
Mastering Mountain Bike Skills is your guide for riding better, faster and more confidently on all terrain. World champion racer Brian Lopes and renowned coach Lee McCormack provide you with all of the key techniques and skills you'll need to take your ride to the next level. This new and improved edition of Mastering Mountain Bike Skills provides detailed, technical instruction for every mountain biking discipline: > Trail > Downhill > Cross-Country > Racing > and more The high-quality photo sequences and demonstrations combined with race stories from Brian Lopes will give you the tools you need, whether you're a recreational rider looking to rock the trails with friends or a rider looking to beat the competition. Let Mastering Mountain Bike Skills help you ride with more confidence and have more fun.
Inhoudsopgave : Chapter 1: Choose Your Weapon Chapter 2: Become One With Your Bike Chapter 3: Make Great Power Chapter 4: Brake Better to Go Faster Chapter 5: Carve Any Corner Chapter 6: Wheelie and Hop Over Anything Chapter 7: Pump Terrain for Free Speed Chapter 8: Drop Like a Feather Chapter 9: Jump With the Greatest of Ease Chapter 10: Flow on Any Trail Chapter 11: Handle Crazy Conditions Chapter 12: Avoid Injuries Chapter 13: Race Like a Champ
Keywords: Mountainbiken